DEVELOPMENT OF ARDUINO-BASED DATA ACQUISITION SYSTEM FOR ENVIRONMENTAL MONITORING USING ZIGBEE COMMUNICATION PROTOCOL - A, Busari Sherif; F, Dunmoye Abibat; F., Akingbade Kayode (APTIKOM Journal on Computer Science and Information Technologies, 2016)
Data Acquisition Systems (DAS) are used for a variety of applications such as environmental monitoring,indoor climate control, health management and medical diagnostics, traffic surveillance and emergency response,disaster management among others. This paper presents the design of a DAS for monitoring environmentaltemperature, pressure and relative humidity. The system employs Arduino Uno microcontroller for signal processingand Zigbee transceivers operating on the 2.4 GHz license-free Industrial, Scientific and Medical (ISM) band ascommunication modules at both the transmitter and receiver ends. While the transmitter board houses the sensors, aGPS module and an LCD, the receiver system is interfaced with a PC which runs a developed MATLAB GUI for datadisplay and analysis and it incorporates an SD card for data storage. The battery-powered system is a low cost, lowpower consumption system which serves as a mini-weather station with real-time data logging, wirelesscommunication and tracking capabilities.